Cyclopecten cancellus Dijkstra 1991 - Dijkstra, Henk H.; Beu, Alan G. (Zenodo, 2018)
Cyclopecten cancellus Dijkstra, 1991 Figs 15H–I,K, 16 Cyclopecten cancellus Dijkstra, 1991: 21, figs 66–70; Dijkstra, 2001: 90, figs 33–35; Dijkstra & Moolenbeek, 2008: 18; Dijkstra & Maestrati, 2008: 97; Dijkstra & Maestrati, 2013b: 474. Type data . Holotype (lv) RMNH56560, 14 paratypes (v) RMNH56561–56566. Type locality: Indonesia, Flores Sea, off SW Salayer, 6°22.4'S 120°26.3'E, dead, 130–155 m (SNELLIUS-II stn 4.153). Additional material examined . — AUSTRALIA: QUEENSLAND : off Cairns, 16°36'12"– 16°35'54"S 146°15'24"– 146°14'18"E, dead, 110–201 m (1 v, C.165464). WESTERNAUSTRALIA : S of Cowaramup Bay, near mouth of Margaret River, 33°57'S 114°59'E, dead (2 v, C.165468); Kilcarnup, N side of Margaret River, 33°57'S 114°59'E, dead, beach (1 v, C.374666); Ellensbrook, 33°55'S 115°0'E, dead, beach (2 v, WAM S12952); Cowaramup, 33°52'S 115°0'E, dead (2 v [rudimentary internal riblets], WAM S12559; 1 v, WAM S12535); Rottnest Island, 32°0'S 115°30'E, dead, beach (9 v, WAM415.91); Rottnest Island, Bathurst Point, 32°0'S 115°30'E, dead, beach (1 v, WAM414.91); Rottnest Island, Ricey Beach, 32°0'S 115°30'E, dead, beach (3 v, WAM413.91; 1 v, C.165465); Cottesloe, Cable Station, 33°0'S 115°45'E, dead (1 v, WAM481.91); NW of Beagle Island, 29°43'S 114°17'E, dead, 274–283 m (1 v, C.165466). — NEW CALEDONIA: off New Caledonia, 20°16'S 169°51'E, alive, 85–100 m (2 pr, C.165234). Figure 16 . Distribution of Cyclopecten cancellus Dijkstra (circles), C. horridus Dijkstra (star), C. powelli Dell (triangle) and C. reticulatus sp. nov. (squares). Description . Shell small, up to c. 3 mm high, convex, subcircular, opaque, whitish to cream, wider than high, inequivalve, almost equilateral, left valve slightly more convex than right, auricles almost equal in size, umbonal angle c. 100°. Left valve with coarse reticulate sculpture with scaly intersections, radial riblets (c. 10) more prominent than commarginal lamellae, both widely spaced, commencing at 0.5 mm shell height and increasing in prominence ventrally, with secondary interstitial radial riblets. Auricles with 1–2 radial riblets crossed by prominent commarginal lamellae. Right valve with closely spaced commarginal lamellae. Anterior auricle with 2–4 weak radial riblets, posterior smooth. Dorsal margin straight. Byssal notch moderately deep, byssal fasciole narrow. Habitat . Living in the sublittoral and bathyal zones amongst rubble on soft bottoms. Distribution . Indonesia, 130–375 m, dead; Vanuatu, 140–175 m, dead (Dijkstra, 1991, 2001); Fiji, 500–614 m, dead (Dijkstra & Maestrati, 2008). Now also from New Caledonia (85–100 m) and Australia (beach drift and 110–283 m, dead). Remarks . The present species is similar to the type specimens from Indonesia, although some specimens from Western Australia have some rudimentary internal riblets, which are lacking in typical specimens. Cyclopecten cancellus is a new record for Australia (empty shells only). : Published as part of Dijkstra, Henk H. & Beu, Alan G., 2018, Living Scallops of Australia and Adjacent Waters (Mollusca: Bivalvia: Pectinoidea: Propeamussiidae, Cyclochlamydidae and Pectinidae), pp. 113-330 in Records of the Australian Museum (Rec. Aust. Mus.) (Rec. Aust. Mus.) 70 (2) on page 149, DOI: 10.3853/j.2201-4349.70.2018.1670, http://zenodo.org/record/5299017